OnabotulinumtoxinA from lines to facial reshaping: A new Italian consensus report. (20th January 2022) - Signorini, Massimo; Piero Fundarò, Salvatore; Bertossi, Dario; Cavallini, Maurizio; Cirillo, Pierfrancesco; Natuzzi, Guglielmo; Quartucci, Sandro; Sciuto, Chantal; Patalano, Mariagrazia; Trocchi, Gloria
Abstract: Background: Botulinum neurotoxin type A is the most widely used nonsurgical treatment for esthetic improvement of the face and neck. In 2015, an Italian consensus panel met to discuss the optimal methods for using onabotulinumtoxinA. However, clinical practice continues to evolve and the original report is now considered obsolete. Aims: To provide updated guidance on the esthetic uses of onabotulinumtoxinA in the face and neck. Methods: A panel of 10 Italian specialists (including plastic and maxillofacial surgeons, dermatologists, and esthetic doctors) individually completed a questionnaire on their own clinical practice, and then met to discuss their responses and agree on a revised treatment consensus. Results: Recommendations are provided on patient assessment, reconstitution of onabotulinumtoxinA, and preferred procedures (injection sites, doses, anatomical targets, safety precautions, etc.) across a variety of treatment areas, including glabellar, crow's feet, and forehead lines; brow lifting and shaping; lower eyelid hypertrophy; bunny lines; sagging nasal tip; gummy smile; masseter hypertrophy; perioral lines; marionette lines and "sad mouth;" mentalis hypertonia; and platysma bands. Some of the recommended doses are substantially increased from the previous consensus (particularly in the upper third and masseter) for the purpose of achieving longer lasting results without affecting safety. Furthermore, two increasingly popular techniques—the Nefertiti lift and Microbotox—are included in the consensus for the first time. Conclusions: Optimal practice with onabotulinumtoxinA requires a systematic approach to maximize safety and effectiveness across the range of potential uses. The present consensus was developed to support these aims.